The Implementation of Principal’s Supervision in SD Negeri Tungkal Ilir Banyuasin (Teacher’s Competency Development Study) - Devi, Devi; Harapan, Edi; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2021)
This study finds out more about the role of principal supervision through the principal functions in improving the professionalism of teachers. The instruments in this study were interview sheet, observation sheet, and documentation study. Data analysis is made after the data and information obtained in accordance with the needs are compiled, classified and formulated on the basis of data interpretation. The results showed that the work program prepared by the principal in fostering teachers has a positive impact on teacher competence. Supervision of the principal is carried out periodically in fostering teachers. This paper contributes to the school in fostering teachers so that they can be more professional in carrying out their duties through supervision carried out by the principal.